Financial Accounting: A Casebook (Book). - Hendrickson, Harvey S.; Hughes, Joint S. (The Accounting Review, 1986)
Abstract Reviews the book "Financial Accounting: A Casebook," by Glenn M. Pfeiffer and Robert M. Bowen.